Investigation of Multibeam Forming Algorithm for Cylindrical Conformal Array Antenna - Ke Zhao; Lizhe Liu; Lirong Mei (International Journal of Antennas and Propagation)
A multibeam forming algorithm based on cylindrical conformal array antenna is proposed in this paper. A comprehensively optimized algorithm of Taylor weights is used to reduce sidelobes. Multiple beams pointed at different azimuth angles are formed based on a reconfigurable overlapping array division method of subarrays, therefore each beam can get the maximum excitation of subarrays and ensure the pointing accuracy of the main lobe. Finally the cylindrical array antenna realizes the multibeam scanning and area coverage. The experimental results show that the sidelobe level after comprehensive optimization is 7.37 dB lower than that without optimization and 1.71 dB lower than that of traditional optimization when a single beam is formed. The comprehensive optimization can eliminate the grating lobe between two beams and reduce the sidelobe to -15 ∼ -20 dB when the two beams are 30°. The left sidelobe is reduced by 2.75 dB and the right sidelobe is reduced by 1.69 dB after comprehensive optimization when the two beams are separated by 40°.